2013
DOI: 10.1038/nbt.2564
|View full text |Cite
|
Sign up to set email alerts
|

Generation of oligodendroglial cells by direct lineage conversion

Abstract: Transplantation of oligodendrocyte precursor cells (OPCs) is a promising potential therapeutic strategy for diseases affecting myelin. However, the derivation of engraftable OPCs from human pluripotent stem cells has proven difficult and primary OPCs are not readily available. Here we report the generation of induced OPCs (iOPCs) by direct lineage conversion. Forced expression of the three transcription factors Sox10, Olig2 and Zfp536 was sufficient to reprogram mouse and rat fibroblasts into iOPCs with morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
251
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(271 citation statements)
references
References 39 publications
17
251
0
3
Order By: Relevance
“…Dabei reicht ein Cocktail von drei Faktoren (Ascl1, Brn2 (Pou3f2) und Myt1l), um Fibroblasten in vitro effizient und schnell in funktionelle Neurone zu konvertieren (Vierbuchen et al, 2010). Spätere Arbeiten derselben Gruppe belegen die Erzeugung oligodendroglialer 34 Vorläuferzel-len (OPC) durch direkte Reprogrammierung (Yang et al, 2013). Diese Zellen werden als interessante Vorläuferzellen zur Therapie myeliner Erkrankungen beschrieben.…”
Section: Direkte Reprogrammierungunclassified
“…Dabei reicht ein Cocktail von drei Faktoren (Ascl1, Brn2 (Pou3f2) und Myt1l), um Fibroblasten in vitro effizient und schnell in funktionelle Neurone zu konvertieren (Vierbuchen et al, 2010). Spätere Arbeiten derselben Gruppe belegen die Erzeugung oligodendroglialer 34 Vorläuferzel-len (OPC) durch direkte Reprogrammierung (Yang et al, 2013). Diese Zellen werden als interessante Vorläuferzellen zur Therapie myeliner Erkrankungen beschrieben.…”
Section: Direkte Reprogrammierungunclassified
“…It remains to be tested whether the factor combinations used in fibroblasts induce the same transmitter identity in PdiNs. Moreover, recent work has expanded the conversion spectrum beyond neurogenesis to generate neural stem cells 19,20 or glial, in particular oligodendrocytes 21,22 . If these reprogramming protocols elicit a similar outcome in adult human brain pericyte-derived cells, this would greatly widen the panorama of applications of this important brain-resident cell type.…”
Section: Conceptual Considerationsmentioning
confidence: 99%
“…After screening of the eight selected transcription factors, three of them (Sox10, Olig2 and Nkx 6.2) turned out to be sufficient to generate iOPCs [8]. Another group, Yang, N et al, showed that a different combination of three transcription factors (Sox10, Olig2, and Zfp536) converted mouse fibroblast to iOPCs [9]. To verify the functionality of iOPCs, they were transplanted into disease model mice.…”
Section: Induced Oligodendrocyte Precursor Cells (Iopcs)mentioning
confidence: 99%
“…To verify the functionality of iOPCs, they were transplanted into disease model mice. 12 weeks after injection, it was demonstrated that iOPCs can differentiate into myelinogenic oligodendrocytes expressing oligodendrocyte markers as well as dense myelin sheaths [9].…”
Section: Induced Oligodendrocyte Precursor Cells (Iopcs)mentioning
confidence: 99%